Omics research project on prospective cohort studies from the Tohoku Medical Megabank Project. (27th April 2018) - Koshiba, Seizo; Motoike, Ikuko; Saigusa, Daisuke; Inoue, Jin; Shirota, Matsuyuki; Katoh, Yasutake; Katsuoka, Fumiki; Danjoh, Inaho; Hozawa, Atsushi; Kuriyama, Shinichi; Minegishi, Naoko; Nagasaki, Masao; et al.
Abstract : Population‐based prospective cohort studies are indispensable for modern medical research as they provide important knowledge on the influences of many kinds of genetic and environmental factors on the cause of disease. Although traditional cohort studies are mainly conducted using questionnaires and physical examinations, modern cohort studies incorporate omics and genomic approaches to obtain comprehensive physical information, including genetic information. Here, we report the design and midterm results of multi‐omics analysis on population‐based prospective cohort studies from the Tohoku Medical Megabank (TMM) Project. We have incorporated genomic and metabolomic studies in the TMM cohort study as both metabolome and genome analyses are suitable for high‐throughput analysis of large‐scale cohort samples. Moreover, an association study between the metabolome and genome show that metabolites are an important intermediate phenotype connecting genetic and lifestyle factors to physical and pathologic phenotypes. We apply our metabolome and genome analyses to large‐scale cohort samples in the following studies. Abstract : We report the design and midterm results of multi‐omics analysis on population‐based prospective cohort studies from the Tohoku Medical Megabank (TMM) Project. We have incorporated genomic and metabolomic studies in the TMM cohort study as both metabolome and genome analyses are suitable for high‐throughput analysis of large‐scale cohort samples.